On the Lathrobium fauna of the Donggong Mountains, eastern China - Peng, Zhong; Li, Qi-Li; Shen, Liang; Gu, Fu-Kang (Zootaxa, 2015)
Material of the paederine genus Lathrobium Gravenhorst, 1802 from the Donggong Mountains, eastern China, is examined. Fifteen species are identified, seven of them described previously and eight undescribed. Seven species are described and illustrated for the first time, all of them micropterous and locally endemic: L. haoae Peng & Li sp. n., L. songi Peng & Li sp. n., L. yui Peng & Li sp. n., L. fengyangense Peng & Li sp. n., L. liyangense Peng & Li sp. n., L. mu Peng & Li sp. n. and L. yani Peng & Li sp. n. One probably undescribed species remains unnamed. The female sexual characters of L. baishanzuense Peng & Li, 2012 and L. zhui Peng & Li, 2014 are described and illustrated for the first time. Including the new taxa, 196 Lathrobium species are currently known from mainland China.